2005
DOI: 10.1007/s10886-005-4251-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis to Divergence of Sex Pheromones in Two Closely Related Moths, Ostrinia scapulalis and O. zealis

Abstract: Crossing experiments between two closely related moths, Ostrinia scapulalis and O. zealis, were conducted to gain insight into the genetic basis of the divergence of female sex pheromones. The sex pheromone of O. scapulalis comprises (E)-11- and (Z)-11-tetradecenyl acetates (E11 and Z11), and distinct genetic variation is found in the blend of components. This variation is largely controlled by a single autosomal locus with two alleles, AE(sca) and AZ(sca). E-type (AE(sca)AE(sca)) females produce a pheromone w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…One group of studies has demonstrated that single genes of large effect can be involved in causing signal divergence among closely related taxa. Changes at single loci underlie differences in pheromone blend among noctuid moth species (Monti et al, 1997), races of European corn borers Dopman et al, 2004) and Ostrinia species (Tabata and Ishikawa, 2005; Table 5). Moreover, an experiment on the cabbage looper (Trichoplusia ni) demonstrated the possible monogenic origin of pheromone divergence in the laboratory: in the course of a study involving collections of volatiles released by females, individuals releasing a new pheromone blend were discovered and one recessive autosomal gene has been shown to be involved in producing the mutant blend (reviewed in Haynes, 1997).…”
Section: Genetics Of Divergence In Chemical Signalsmentioning
confidence: 99%
“…One group of studies has demonstrated that single genes of large effect can be involved in causing signal divergence among closely related taxa. Changes at single loci underlie differences in pheromone blend among noctuid moth species (Monti et al, 1997), races of European corn borers Dopman et al, 2004) and Ostrinia species (Tabata and Ishikawa, 2005; Table 5). Moreover, an experiment on the cabbage looper (Trichoplusia ni) demonstrated the possible monogenic origin of pheromone divergence in the laboratory: in the course of a study involving collections of volatiles released by females, individuals releasing a new pheromone blend were discovered and one recessive autosomal gene has been shown to be involved in producing the mutant blend (reviewed in Haynes, 1997).…”
Section: Genetics Of Divergence In Chemical Signalsmentioning
confidence: 99%
“…Therefore, it often is considered as a powerful force for reproductive isolation and, thus, speciation (Cardé and Baker 1984). Some studies with closely related species have shown that reproductive isolation under natural conditions is the result of differences in sex pheromone systems, as these species can hybridize when confined in the laboratory (Gadenne et al 1997;Huang et al 2002;Tabata and Ishikawa 2005;Laurent et al 2007). Traditionally, sex pheromone communication systems in moths have been assumed to involve strong stabilizing selection on emitters and receivers, and such stabilizing pressure would allow only small, incremental changes in pheromone systems over time (Paterson 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the genetics of pheromonal differences in moths have focused on changes in pheromone blends that can be explained by alteration in one or two enzymes, or by the sequence of chain-shortening and desaturation events (e.g., Lö fstedt, 1993;Cossé et al, 1995;Haynes, 1997;LaForest et al, 1997;Roelofs and Rooney, 2003;Dopman et al, 2004;Tabata and Ishikawa, 2005). The differences between the multi-component pheromone blends of females of many moth species, such as Heliothis virescens (Hv) and Heliothis subflexa (Hs), cannot be explained by one enzyme (Jurenka, 2004), because compounds with three different functional groups (alcohols, aldehydes, and acetate esters) and two different chain lengths (C14 and C16) are involved (see Table 1 and Fig.…”
Section: Introductionmentioning
confidence: 99%